Retenção discente nos cursos de graduação do Centro Universitário do Norte do Espírito Santo implantados a partir do REUNI - Barcelos Júnior, Alexandre (2015)
The objective of this study was to analyze the considerations about the student's success in the context of higher education and investigate the causes for student retention or prolonged permanence in the Courses of Computing Science (Bachelor Degree), Biological Sciences (Graduation) Physics, Mathematics and Chemistry offered in Centro Universitário do Norte do Espírito Santo - CEUNES which were implanted following the proposed by the Program REUNI. Since the student retention is a condition that leads the student to fail in meeting the deadline for completing the course in time we decided to investigate the causes of the phenomenon and its relation to the Program. The methodology adopted was a qualitative and quantitative research. It is a descriptive, explanatory research. The instruments adopted were interviews, questionnaire and institutional reports. The content analysis was used to dialogue with the results of the interviews. The sample involved coordinating teachers and managers of the courses in question and students classified in moderate and severe retention levels. The main symptom identified for retention is the failure in compulsory subjects. The causes given were institutional, external and personal. The predominant cause was the institutional, which most often cited factors by students were: the teaching methods of the teachers, learning difficulties and irregular offer of disciplines. The most cited external factors were related to work, health or family issues. Personal factors were learning difficulties caused by poor elementary and high school formation and lack of dedication, influenced by the double shift (work/studies) or by student immaturity. It was identified negative influence of student retention in graduation target established by REUNI (which was established to reach 90% of graduation conclusion). The proposed actions were based on student's success and the main ones were: keep the offer of the disciplines monthly, specially the main ones; expand the tutoring and educational support programs, particularly for students with learning difficulties; and promote the continuous improvement of the educational practices of teachers.